(untitled) (Journal of the College of Education for Women, 2019)
Research on geopolitical and geopolitical studies relates to a range of sciences that can be called auxiliary sciences, such as political science, international relations in particular, and history, but their focus is rarely on science and ethnography That the issues and problems of the world today has become so large and complex that does not allow a specific field or knowledge to solve one of the need for the newly known knowledge integration (geopolitics and geopolitics) in particular to move towards cognitive integration to understand many of the problems and global issues that faced The importance of this study comes to clarify the relationship between Darwinism, geopolitics and geopolitics. The geopolitics in modern terms did not come from a vacuum, especially the idea of ​​the "vital field" Which had been affected by social Darwinism and had had an impact on the geographical expansion of colonialism and the resulting calamities and wars. The research attempts to reveal the view of Western civilization of these concepts and theories and explain the position of Islam and try to compare the two sides.